2018
DOI: 10.3802/jgo.2018.29.e95
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA XLOC_006390 facilitates cervical cancer tumorigenesis and metastasis as a ceRNA against miR-331-3p and miR-338-3p

Abstract: ObjectiveCervical cancer is one of the most common malignant tumors. Our previous results showed that long non-coding RNA (lncRNA) XLOC_006390 plays an important role in cervical cancer. In this study, we have explored the mechanism of action of lncRNA XLOC_006390.MethodsLncRNA XLOC_006390 was proposed to exercise its function as a competing endogenous RNA (ceRNA), and its potential targeted miRNAs was predicted through the database LncBase Predicted v.2. Two miRNAs, miR-331-3p, and miR-338-3p, were chosen for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
133
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 166 publications
(145 citation statements)
references
References 46 publications
6
133
2
Order By: Relevance
“…Generally, miRNAs exert their functions by direct cleavage and/or translational inhibition of target mRNAs. Recently, it has been reported that miR‐331‐3p has several targets in different cancers, such as PHLPP in hepatocellular cancer, ST7L in pancreatic cancer and NRP2 in cervical cancer . ErbB2 was also reported to be a target of miR‐331‐3p, but the signaling pathway that was regulated by miR‐331‐3p that targeted ErbB2 was unknown.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Generally, miRNAs exert their functions by direct cleavage and/or translational inhibition of target mRNAs. Recently, it has been reported that miR‐331‐3p has several targets in different cancers, such as PHLPP in hepatocellular cancer, ST7L in pancreatic cancer and NRP2 in cervical cancer . ErbB2 was also reported to be a target of miR‐331‐3p, but the signaling pathway that was regulated by miR‐331‐3p that targeted ErbB2 was unknown.…”
Section: Discussionmentioning
confidence: 99%
“…14 However, other researchers discovered antitumor functions of miR-331-3p in urothelial cancer, 29 gastric cancer, 16 and cervical cancer. 17 The functions of miR-331-3p in NSCLC were also ambiguous, 30 14 and NRP2 in cervical cancer. 17 ErbB2 was also reported to be a target of miR-331-3p, 16 but the signaling pathway that was regulated by miR-331-3p that targeted ErbB2 was unknown.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations